A Meta-analysis of improvement of the nutritional status with whey protein in patients with maintainable hemodialysis - ZHANG Cheng-hua; SHENG Mei-xiao (Linchuang shenzangbing zazhi)
Objective To evaluate the efficacy of whey protein in improving nutritional status in maintenance hemodialysis(MHD)patients.Methods We systematically searched the PubMed,Web of science,Cochrane Library,Embase,CNKI,CBM,VIP and Wan-Fang databases from their inception to November 10 th,2019.Two researchers screened and extracted the literature independently based on the inclusion and exclusion criteria.The Cochrane Risk Assessment Tool was used to evaluate risk of bias for the included literature.Finally,we used Review Manager 5.3 software to conduct the meta-analysis.Results A total of 1029 papers as related literature were available in our search,and 9 ones of the papers were included finally,involving a total of 525 patients.The Meta-analysis showed that,compared with the control group,whey protein could raise the serum albumin level of the patients [OR=0.22,95%CI(0.07,0.37),P=0.004],improve serum creatinine levels [OR=-0.45,95%CI(-0.89,-0.01),P=0.03],and reduce the phosphorus load [OR=-0.45,95%CI(-0.89,-0.01),P<0.01].What’s more,in subgroup analysis,when whey protein was used as an additional supplement it seemed to be more significantly improve serum albumin(P<0.01),with statistically significant difference between the subgroups.Conclusions Whey protein can improve the nutritional level of MHD patients.However,due to fewer study samples included and the lack of clinical long-term indicators,the conclusion is still to validate further by more long-term,high-quality,large-sample,multicenter,randomized double-blind clinical trials.